Pengaruh Kualitas Layanan Pendidikan, Budaya Sekolah, Citra Sekolah Terhadap Kepuasan Orang Tua - Nobita Triwijayanti; Herry Sanoto; Mila Paseleng (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
The aim of this study was to find out the effect of education services quality, school cultures, and school images toward parental satisfactions. This study is a quantitative study using path analysis to find out the effect of each variable on parental satisfactions. This study used questionnaires, interviews and documentation instruments. The subjects on this study were parents. The results on this study showed that there were positive influences of educational services quality, school cultures, and school images on parental satisfactions. it shows the effect of 60.7% and 40.3% is influenced by other factors. The findings on this study are educational service satisfactions which has the biggest role in parental satisfactions, followed by school cultures and school images.